2017
DOI: 10.1038/s41598-017-15862-z
|View full text |Cite
|
Sign up to set email alerts
|

The genomic landscape of Nepalese Tibeto-Burmans reveals new insights into the recent peopling of Southern Himalayas

Abstract: While much research attention has focused on demographic processes that enabled human diffusion on the Tibetan plateau, little is known about more recent colonization of Southern Himalayas. In particular, the history of migrations, admixture and/or isolation of populations speaking Tibeto-Burman languages, which is supposed to be quite complex and to have reshaped patterns of genetic variation on both sides of the Himalayan arc, remains only partially elucidated. We thus described the genomic landscape of prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 45 publications
8
35
0
Order By: Relevance
“…A Sherpa individual from the Rolwaling Himal (Gaurishankar Conservation Area, GCA, Dolakha District, Nepal), who was third-generation native of the Rolwaling Sherpa community (i.e., with both parents and grandparents born in the village of Beding at 3,690 m a.s.l. ), was chosen among those recruited during several sampling campaigns ( Gnecchi-Ruscone et al. 2017 ) organized in collaboration with the ExPlora Nunaat International nonprofit organization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Sherpa individual from the Rolwaling Himal (Gaurishankar Conservation Area, GCA, Dolakha District, Nepal), who was third-generation native of the Rolwaling Sherpa community (i.e., with both parents and grandparents born in the village of Beding at 3,690 m a.s.l. ), was chosen among those recruited during several sampling campaigns ( Gnecchi-Ruscone et al. 2017 ) organized in collaboration with the ExPlora Nunaat International nonprofit organization.…”
Section: Methodsmentioning
confidence: 99%
“…2017 ) organized in collaboration with the ExPlora Nunaat International nonprofit organization. This subject was selected to be representative of the Rolwaling Sherpa population, presenting 100% of the “Sherpa-like” genetic component observed in previous studies ( Gnecchi-Ruscone et al. 2017 ) and a high-altitude adapted phenotype (i.e., he is a professional mountaineer and Himalayan Guide who have climbed Mount Everest several times).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the South Asian population(s) with whom the incoming Southeast Asians mingled were AASI related with little to no West Eurasian ancestry fraction [27]. Finally, it has been showed that the Tibeto-Burmans (ATBs) derived their ancestry through admixture with low-altitude East Asians who migrated from China and likely across Northern India or Myanmar [28] leading to the high genomic proximity between South Asians of ATB ancestry and East Asians.…”
Section: South Asians: a Variegated Canvas For Covid-19mentioning
confidence: 99%
“…Hence, mutational landscape often refers to sequence variations leading to diseases; such as, with reference to cancer. [19][20][21] On the other hand, nucleotide sequence variations consistent with positive impressions; such as with respect to adaptation 22 and tolerance; 23,24 or neutral impressions such as allelic variations within species; [25][26][27][28] tends to be referred to as genomic landscape. However, the opposite may also be true as mutational landscape had also been used to describe natural variations between species.…”
Section: Intracellular Landscapesmentioning
confidence: 99%
“…32 The essential genes in B. breve include (a) housekeeping genes; such as, DNA replication and transcription, manufacture of cell envelope components, the Secdependent protein translocation pathway; (b) genes in central pathways for energy acquisition and conversion; such as central glycolysis, a specific bifid-shunt, pentose phosphate pathway, and pathways crucial for production of energy and precursors for other metabolic routes; (c) genes encoding subunits of ATP synthase; (d) genes encoding enzymes involved in purine and pyrimidine synthesis; and (e) genes encoding proteins involved in ion transport and redox homeostasis. Lastly, Gnecchi-Ruscone et al, 25 successfully genotyped 59 buccal swab from 4 communities near the Tibetan plateaus. By analyzing the SNPs, a model to describe the migration and colonization of Southern Himalayan slopes from East Asia ancestry is proposed.…”
Section: Intracellular Landscapesmentioning
confidence: 99%